Rancang Bangun Pemantauan Cairan Infus Dengan Arduino Nano Berbasis Android - Putung, Yoice Rita; Noya, Donald; Aror, Ventje; Sundah, Josephin; Patabo, Muchdar (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2023)
Pantauan pemberian cairan berisi vitamin dan mineral melalui botol ke pembuluh darah (infus) dengan kebiasaan yang lama, yakni (mengontrol keadaan kantong infus pada orang sakit dengan spontan. Jika ada gangguan seperti cairan infus tersumbat, kemacetan dan kehabisan cairan infus, akan berbahaya bagi orang sakit jika tidak segera ditangani. Penelitian ini bertujuan untuk mendeteksi cairan infus dengan sensor berat (load cell ) dan jika terjadi penyumbatan pada selang infus dengan sensor Line Proximity (infrared proximity) yang dikendalikan dengan mikrokontroler Arduino nano kemudian hasilnya dimonitoring pada LCD dan smartphone Android dengan aplikasi blink. Kemudian bila terjadi penyumbatan atau cairan infus habis buzzer akan berbunyi dengan tujuan memberikan informasi kepada perawat. Berdasarkan hasil pengujian yang telah dilakukan alat dapat mendeteksi berat cairan infus = 500 ml,. berat cairan infus habis = 36 ml, cairan tersumbat , monitoring pada LCD dan Android.Monitoring the administration of fluids containing vitamins and minerals through bottles into blood vessels (infusions) with long-standing habits, namely (spontaneously controlling the condition of infusion bags in sick people. If there are disturbances such as blocked infusion fluids, congestion and running out of infusion fluids, it will be dangerous for people sick if not treated immediately. This study aims to detect infusion fluids with a weight sensor (load cell) and if there is a blockage in the infusion hose with a Line Proximity (infrared proximity) sensor controlled by an Arduino nano microcontroller then the results are monitored on the LCD and Android smartphone with the blink application. Then if there is a blockage or the infusion fluid runs out the buzzer will sound with the aim of providing information to the nurse. Based on the results of the tests that have been carried out, the tool can detect the weight of the infusion fluid = 500 ml. the weight of the infusion fluid is used up = 36 ml, the fluid is blocked, monitoring on the LCD and Android.